Installment financial transactions through the procurement process of Islamic cooperatives in Pattani Province - Sideh, Wayooso; Al-Faritiy, Ahmad; Samaoh, Ismaae; Chapakiya, Abdurrahman (Al-HIKMAH Journal, 2024)
Abstract Abstract The objectives of this research are 1) to analyze and collect data on procurement and installment finance transactions in Islam. 2) to study the practice of installment finance transactions of Islamic cooperatives in Pattani Province. Study methods. This time it was qualitative research. Data were collected through in-depth interviews with key informants, including 8 cooperative executives and 3 Islamic scholars. Data were analyzed using content analysis. Based on descriptive statistics (Descriptive Statistics) Results of the study: Installment financial transactions through the procurement process of Islamic cooperatives in Pattani Province are consistent with the spirit of Shariah principles. In practice and operations, it was found that 1. Treatment of investors related to inspiring investors is 1) Reward for interest in investing. 2.Opportunity for purchasing and selling is only given to those who join as members. Installment payments are in accordance with the spirit of the Shariah. 3. Conducting other matters such as Wadi'ah as well as Al-Sarfu, etc. Conducting according to the rules of the Shariah. Suggestions 1. Cooperative executives must set strategic plans, analyze and plan strategies with clear indicators. 2. The operations of the cooperative must be in accordance with the rules and regulations of the cooperative. 3. The practice and management of installment purchasing is in accordance with Shariah principles and risk management rules. 4. Cooperative executives must assign officials to randomly review the debt of cooperative members regularly to prevent bad debt from occurring. 5. Executives must be prepared. and can provide funds to enhance liquidity by being able to pay off debts or an obligation that is due and payable accurately and at a reasonable cost.